Current and emerging immunotherapeutic approaches to treat and prevent peanut allergy. (December 2012) - Miller, Darren S; Brown, Michael P; Howley, Paul M; Hayball, John D
Peanut-allergen hypersensitivity reactions, which can result in anaphylactic episodes and death, affect approximately 1% of the general population. Currently, strict avoidance of allergenic food is the only available treatment for this food-induced allergic reaction; however, the innocuous presence of trace amounts of peanut protein contaminating food products makes avoidance extremely difficult, especially in children. Therefore, safe and inexpensive therapeutic strategies aimed at prevention and treatment of peanut allergies is urgently required. This review summarizes the current state of knowledge of adaptive immune recognition and responsiveness to peanut allergens and how this can be integrated and subverted into new therapeutic treatment regimens for these dangerous allergic responses. The potential for new strategic vaccination-based interventions to either moderate or prevent these types of responses from occurring is also discussed.